(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The research aims to achieve sustainable competitive advantage by hearing the customer’s voice and paying attention to his desires and requirements in Baghdad Soft Drinks Company. The research problem was through questions raised about the relationship and effect of hearing the customer’s voice in achieving the competitive advantage of Baghdad Soft Drinks Company. To achieve the research goal, two main hypotheses were tested. And a secondary one, and the questionnaire was used as a tool to collect data by distributing (137) questionnaires from which (100) questionnaires were retrieved for analysis, and the data were analyzed using the (Spss) program, and the research reached a good level in terms of the researched company’s interest in the voice of its customers in addition to an investigation My relationship and the impact between the customer’s voice and the sustainable competitive advantage, and the research recommended many recommendations, the most important of which is conducting periodic interviews with the company’s customers and paying attention to their desires and suggestions about developing and improving the company’s products.